Examen especial al rubro activos en la clínica María Auxiliadora del cantón Sucúa, período 2015 - Garzón Maldonado, Zoila Guadalupe (2017)
The research was developed in compliance with a prerequisite to opt for the degree of Accounting and Audit Engineer, Public Accountant Auditor. The work was carried out in accordance with the provisions of the Internal Control Standards (NCI), International Accounting Standards, Generally Accepted Auditing Standards (NAGA's), and Generally Accepted Accounting Principles (GAAP). The objectives set out in the Special Examination of the Assets of the María Auxiliadora Clinic were achieved through the application of Internal Control programs and questionnaires, allowing the Asset to be evaluated, evidencing non-compliance with Internal Control Standards, Generally Accepted Auditing Standards. and Generally Accepted Accounting Principles for the management of economic resources. In the process of the Examination the three phases were applied: Planning, Execution and Communication of Results, for which techniques and procedures were used that allowed to obtain information of the item under examination. The results of the Exam are communicated in the Final Report, which contains comments, conclusions and recommendations, observing the non-compliance of Internal Control Standards, such as: Daily income and expenses are not recorded properly; there is no ordering of the files; no surprise arcs are practiced; no bank reconciliations are carried out; the staff is not warranted; staff is not trained; the provision for Uncollectable Accounts has not been considered; the inventories are not made by an independent person; The buildings, vehicles and medical equipment items are not insured; and, the inventories of Furniture and Equipment, Medical Equipment are outdated. For this purpose, the Schedule of Recommendations should be considered in order to improve the efficiency, effectiveness and economy of this entity.